Substance of politics - Appadorai , A. (Madras, 1968)
IN preparing this new edition care has been taken to make a thorough revision of the text. Besides, a new chapter has been added on the Republic of South Africa; the chapter on Pakistan has been completely rewritten to take into account the new Constitution adopted in 1962; a section has been added on India, a member of the Commonwealth; and the bibliographies have taken note of the growing literature on the subject.
Keywords: Politics